2021
DOI: 10.1016/j.molmet.2021.101321
|View full text |Cite
|
Sign up to set email alerts
|

Salsalate reduces atherosclerosis through AMPKβ1 in mice

Abstract: Objective Salsalate is a prodrug of salicylate that lowers blood glucose in people with type 2 diabetes. AMP-activated protein kinase (AMPK) is an αβγ heterotrimer which inhibits macrophage inflammation and the synthesis of fatty acids and cholesterol in the liver through phosphorylation of acetyl-CoA carboxylase (ACC) and HMG-CoA reductase (HMGCR), respectively. Salicylate binds to and activates AMPKβ1-containing heterotrimers that are highly expressed in both macrophages and liver, but the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Inhibition of this regulatory mechanism results in the development and progression of atherosclerosis, suggesting that direct targeting of the AMPK-HMGCR signalling cascade may be an attractive therapeutic option for suppressing the development and progression of atherosclerosis and thus reduce cardiovascular risks. These findings provide a mechanistic basis to support the use of AMPK activators such as salsalate [ 25 ], O-304 [ 47 ] and PXL 770 [ 48 ] for reducing atherosclerotic cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Inhibition of this regulatory mechanism results in the development and progression of atherosclerosis, suggesting that direct targeting of the AMPK-HMGCR signalling cascade may be an attractive therapeutic option for suppressing the development and progression of atherosclerosis and thus reduce cardiovascular risks. These findings provide a mechanistic basis to support the use of AMPK activators such as salsalate [ 25 ], O-304 [ 47 ] and PXL 770 [ 48 ] for reducing atherosclerotic cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 92%
“…In the context of atherosclerosis, AMPK has been shown to have multiple anti-atherogenic effects through its influence on inflammatory signalling [ 17 ], suppressing monocyte to macrophage differentiation [ 18 , 19 ], and increasing cholesterol efflux [ 20 , 21 ], which in combination, decreases foam cell formation and atherogenesis. In line with this, systemic infusion of direct or indirect AMPK activators such as A769662, salsalate or metformin has been shown to decrease lesion size in atherosclerotic prone mice [ [22] , [23] , [24] , [25] ].…”
Section: Introductionmentioning
confidence: 95%
“…It was found that Schisandra chinensis fruit (SF) extract may decrease lipid accumulation by upregulating AMPK and downregulating HMGR ( 38 ). A study showed that salsalate reduces atherosclerosis through AMPK, which inhibits fatty acid and cholesterol synthesis through the phosphorylation of HMGCR in mice ( 47 ). Sterol regulatory element-binding protein (SREBP1) is found to particularly involve in the activation of the genes controlling fatty acid metabolism and de novo lipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the multifaceted effects of salicylate on various cell types remain unclear. Recently, a novel action of salicylate was discovered, with a recent study showing that it activates AMPK by binding to the A-769662 drug-binding site on the AMPK β1 subunit 16 . Through this mechanism, salicylate reportedly improves atherosclerosis and fatty liver 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel action of salicylate was discovered, with a recent study showing that it activates AMPK by binding to the A-769662 drug-binding site on the AMPK β1 subunit 16 . Through this mechanism, salicylate reportedly improves atherosclerosis and fatty liver 16 , 17 . However, the role of salicylate in wound healing remains unclear.…”
Section: Introductionmentioning
confidence: 99%